Bioactivity of microbial biofilms in extreme environments - Bhat, Shriya P.; Roach, David J. (Frontiers in Microbiology, 2025)
Biofilms, which are highly structured microbial communities encased in a self-produced matrix, are frequently employed by many bacteria and archaea with significant implications for their survival in extreme environments. These environments, characterized by extreme temperatures, pH, salinity, and variable nutrient availability, can pose challenges that biofilms help organisms overcome through unique adaptations. This review explores the bioactivity of biofilms in extreme environments, highlighting biofilms’ ability to produce novel biomolecules and other biofunctions with potential applications in medicine and biotechnology. Key adaptations such as extracellular polymeric substances, cooperative and competitive interactions, and specialized nutrient acquisition strategies are examined for their roles in biofilm resilience and bioactivity. The potential of these biofilms to contribute to the development of novel therapeutics, antimicrobial agents, antioxidants, and anticancer compounds is discussed, underscoring their significance in advancing medical and biotechnological applications. Through an in-depth analysis of current knowledge, this review highlights the bioactive capacities of extremophilic biofilms and their promising applications for human benefit.